PENDAMPINGAN PEMBUATAN E-MODUL BERDIFRENSIASI BERMUATAN LITERASI SAINS PADA KURIKULUM MERDEKA DI SDN 1 SENGKERANG - Pahru, Syaipul; Pransisca, Made Ayu; Marzuki, Ahmad Dedi; Rismawati, Lia; Sahabudin, Sahabudin; Nurpitasari, Nopi; Mastum, Mastum (LPPM Institut Pendidikan Nusantara Global, 2023)
Differentiated learning is a concept that has long been known since NCLB (2002-2015), then reinforced again in the Independent Curriculum. The aim of this mentoring activity is to increase teachers' knowledge and understanding in developing differentiated e-modules containing scientific literacy. Differentiated learning is closely related to the global education agenda, namely emphasizing scientific literacy which is associated with socioscientific issues. The participants in this activity were 12 teachers at SDN 1 Sengkerang. Mentoring activities use one-group pre- and post-test workshop design with material exposure sessions and practice sessions using the peer instruction method. This mentoring activity was concluded to be effective because it was able to increase participants' gains in the very satisfactory category. Apart from that, teachers also experience understanding, adaptability and flexibility in developing differentiated e-modules containing scientific literacy.